Repetitive Transcranial Magnetic Stimulation (rTMS) Improves the Gait Disorders of Rats Under Simulated Microgravity Conditions Associated With the Regulation of Motor Cortex - Yang, Jiajia; Liang, Rong; Wang, Ling; Zheng, Chenguang; Xiao, Xi; Ming, Dong (Frontiers in Physiology, 2021)
In previous studies, it has been proved that repetitive transcranial magnetic stimulation (rTMS) improves dyskinesia induced by conditions such as spinal cord injury, Parkinson diseases and cerebral ischemia. However, it is still unknown whether it can be used as a countermeasure for gait disorders in astronauts during space flight. In this study, we evaluated the effects of rTMS on the rat gait function under simulated microgravity (SM) conditions. The SM procedure continued for consecutive 21 days in male Wistar rats. Meanwhile, the high-frequency rTMS (10 Hz) was applied for 14 days from the eighth day of SM procedure. The behavioral results showed that SM could cause gait disorders such as decreased walking ability and contralateral limb imbalance in rats, which could be reversed by rTMS. Furthermore, rTMS affected the neural oscillations of motor cortex, enhancing in δ (2-4 Hz) band, suppressing in Ө (4-7 Hz) and α (7-12 Hz) bands. Additionally, rTMS could activate mTOR in the motor cortex. These data suggests that the improvement effects of rTMS on gait disorders in rats under SM conditions might be associated with its regulation on neural oscillations in the cerebral motor cortex and the expression of some motor-related proteins which may enhance the control of nervous system on muscle function. Based on our results, rTMS can be used as an potential effective supplement in the field of clinical and rehabilitation research to reduce gait disorders caused by the space environment.